THE CONCEPT OF THE CRIME FACILITATOR: TYPES OF ASSISTANCE - Poghosyan, Sevak (State and Law, 2021)
The article discusses the issues of qualifying the actions of the facilitator, defining their exhaustive list by law, as well as other problematic issues. Based on the research, the author concludes that there is no need to provide an exhaustive list of the actions of the facilitator, suggests referring to the relevant article of the General Part when qualifying the action of a person who is even just a member of an organized group or criminal cooperation and has committed the crime being a part of them.